2007
DOI: 10.1080/15459620701322645
|View full text |Cite
|
Sign up to set email alerts
|

Unmetabolized Polycyclic Aromatic Hydrocarbons in Urine as Biomarkers of Low Exposure in Asphalt Workers

Abstract: The aim of the study was the assessment of low-level exposure to polycyclic aromatic hydrocarbons (PAHs) by biological monitoring focusing on measurement of unmetabolized PAHs in urine. Italian asphalt workers (AW, n = 100) and roadside construction workers (CW, n = 47) were investigated by measurement of unmetabolized PAHs and 1-hydroxypyrene (OH-Py) in urine spot samples collected respectively after two days of vacation (baseline), before and at the end of the monitored workshift, in the second part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
2
20
1
Order By: Relevance
“…This finding lends indirect support to the conjecture that urinary levels of Nap and Phe reflect the corresponding air levels of these compounds in occupational settings at the time of urine collection. Our results support those from a recent study by Campo et al ,25 which showed that measurements of urinary Nap and Phe in highway construction workers and asphalt workers were highly correlated with personal airborne exposures to these compounds.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding lends indirect support to the conjecture that urinary levels of Nap and Phe reflect the corresponding air levels of these compounds in occupational settings at the time of urine collection. Our results support those from a recent study by Campo et al ,25 which showed that measurements of urinary Nap and Phe in highway construction workers and asphalt workers were highly correlated with personal airborne exposures to these compounds.…”
Section: Resultssupporting
confidence: 92%
“…The ranks of observed Nap and Phe levels are consistent with a priori reports of PAH exposures,14 where coke-oven workers had the highest concentrations (top > side and bottom > steel-factory controls),13 19 followed by asphalt workers (paving > milling),20 21 followed by diesel-exposed workers. We note that the asphalt workers’ Nap and Phe levels in urine are similar to median levels measured by Campo et al in road paving workers and road construction workers 24 25. We also note that the control workers from the Chinese steel-making complex had higher levels of Nap and Phe in their urine than even the asphalt workers, indicating a significant source of background exposure to PAHs in the air of that factory.…”
Section: Resultssupporting
confidence: 85%
“…One of the most reliable biological markers for exposure assessment of PAHs is the detection of PAH and their metabolites in urine samples obtained from exposed individuals (2,(30)(31)(32)(33)(34)(35)(36)(37)(38). PAHs, such as pyrene, undergo biological oxidation utilizing microsomal enzymes to yield oxidative products which can either react with DNA or protein, or be further metabolized and subsequently eliminated from the body in the form of more water soluble products, such as glucuronide and sulfate conjugates (39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolites of PAHs with two or three aromatic rings are mainly excreted in urine, while larger PAH metabolites are mainly excreted in faeces 3. A small percentage of PAH intake is excreted as unmetabolised compounds 4 5…”
mentioning
confidence: 99%